Assessment of drug hypersensitivity with non-irritating concentrations of antibacterial agents for allergic skin tests: a review - Biswas, Pritam; Anuradha, H. V.; Shivamurthy, M. C. (International Journal of Basic & Clinical Pharmacology, 2017)
Hypersensitivity reactions to antibiotics are common with a prevalence of 6-10% of all adverse reactions. There is a lack of guidelines and standardization of skin tests for the screening of hypersensitivity to all antibiotics, in terms of the methodology, dose and time of evaluation of the tests. Literature from Europe and America suggests the use of non-irritating concentration (NIC) of antibiotics for skin testing such as intra dermal test (IDT), skin prick test (SPT). These are concentrations at which the drug is unlikely to produce irritation by virtue of its chemical nature resulting in false positive reactions. These concentrations have been validated by trials in their populations. Due to the increase of antibiotic resistance in our country, declaring a patient allergic to a specific class of antibiotics based on positive skin tests can further narrow the therapeutic armory. These individuals have an increased incidence of infections with resistant organisms as well as increased cost of hospitalization. This is due to the use of alternative broad spectrum antibiotics. Therefore, there is a need for a standardized protocol for the use of skin tests in screening of hypersensitivity, with validated NIC of all antibacterial agents. The aim of this article is to review literature of protocols for assessment of drug hypersensitivity with NIC of antibacterial drugs for SPT, IDT and also establish the need for research in this area in our country.